2014
DOI: 10.1155/2014/676304
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Health Beliefs of Women with Increased Risk of the Female Athlete Triad

Abstract: Women with increased risk of the female athlete triad (Triad) are more susceptible to osteoporosis compared to other women. The study included 65 women with increased risk of the Triad who had their osteoporosis health beliefs measured to assess their concern for the disease. Participants were female collegiate cross-country runners at different levels of competition, including National Association of Intercollegiate Athletics (NAIA) and National Collegiate Athletic Association (NCAA) Divisions III, II, and I.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Nguyen, Wang, and Waigandt (2012) found that female college students, even while enrolled in a health education course, only had low to moderate perceived susceptibility to osteoporosis and moderate perceived severity of osteoporosis, and concluded that their low concern was likely due to the distal time of onset of osteoporosis. Consistent findings by Nguyen, Wang, and Okamura (2014) showed that female collegiate cross-country runners, who are at increased risk of the female athlete triad and of osteoporosis, also only had low to moderate perceived susceptibility to osteoporosis and moderate perceived severity of osteoporosis. Gammage et al (2009) found that women had higher perceived susceptibility to and severity of osteoporosis than those who restricted their dietary intake, which suggests that women know restrictive diets leads to osteoporosis.…”
mentioning
confidence: 58%
“…Nguyen, Wang, and Waigandt (2012) found that female college students, even while enrolled in a health education course, only had low to moderate perceived susceptibility to osteoporosis and moderate perceived severity of osteoporosis, and concluded that their low concern was likely due to the distal time of onset of osteoporosis. Consistent findings by Nguyen, Wang, and Okamura (2014) showed that female collegiate cross-country runners, who are at increased risk of the female athlete triad and of osteoporosis, also only had low to moderate perceived susceptibility to osteoporosis and moderate perceived severity of osteoporosis. Gammage et al (2009) found that women had higher perceived susceptibility to and severity of osteoporosis than those who restricted their dietary intake, which suggests that women know restrictive diets leads to osteoporosis.…”
mentioning
confidence: 58%